iTake-over : the recording industry in the digital era - Arditi, David, 1982- (Rowman and Littlefield, 2015)
ITake-Over: The Recording Industry in the Digital Era sheds light on the way large corporations appropriate new technologies related to recording and distribution of audio material to maintain their market dominance in a capitalist system.